Theorising Language in Organisational Research: Three Views - Brocklesby, John; Jones, Deborah; Riad, Sally (School of Management Working Papers, 2011)
This paper advocates a proposition: that good language-based organisational research must pay attention to theorising language itself. It takes the form of a dialogue between three interpretive perspectives: Maturana’s theory of the observer, foucauldian discourse analysis, and social constructionism. The paper concludes that theorising links between language and research in organisational settings can contribute both to more rigorous research and to the body of language based research generally.